Cover Image. (18th December 2017) - Tonkin, Jonathan D.; Altermatt, Florian; Finn, Debra S.; Heino, Jani; Olden, Julian D.; Pauls, Steffen U.; Lytle, David. A.
Abstract : The cover image created from a digital elevation model sourced from the HydroSHEDS database by J. D. Tonkin et al., is based on the Special Issue Article The role of dispersal in river network metacommunities: Patterns, processes, and pathways, DOI:10.1111/fwb.13037 . Source: HydroSHEDS Technical Documentation. World Wildlife Fund US, Washington, DC.